2007
DOI: 10.1177/1077559507300643
|View full text |Cite
|
Sign up to set email alerts
|

The Sacramento Dependency Drug Court: Development and Outcomes

Abstract: Dependency Drug Courts (DDCs) are a growing method of addressing the functional status and reunification success of families involved in child welfare and affected by substance use disorders. Despite widespread interest in DDCs, few evaluations have appeared in the literature to help inform the discussion about their effectiveness. This article provides a description of various types of DDCs and reports 24-month reunification rates from the Sacramento DDC. Results indicated that DDC participants had higher rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 1 publication
0
71
0
Order By: Relevance
“…Research on families in child welfare, parents in treatment, and families of substance-exposed infants suggests that a majority of families involved or at risk for involvement in the child welfare system in the United States are impacted by parental substance abuse problems (Boles, Young, Moore, & DiPirro-Beard, 2007;Carter & Myers, 2007;Connell-Carrick, 2007;Smith, Johnson, Pears, Fisher, & DeGarmo, 2007;Vanderploeg, Caron, Saunders, Katz, & Tebes, 2007;Young, Boles, & Otero, 2007). Concern over the correlation between substance abuse and child welfare, as well as growing recognition of the importance of consistency in caretaking in child development, has generated a number of policy changes on both national and state levels.…”
Section: Introductionmentioning
confidence: 99%
“…Research on families in child welfare, parents in treatment, and families of substance-exposed infants suggests that a majority of families involved or at risk for involvement in the child welfare system in the United States are impacted by parental substance abuse problems (Boles, Young, Moore, & DiPirro-Beard, 2007;Carter & Myers, 2007;Connell-Carrick, 2007;Smith, Johnson, Pears, Fisher, & DeGarmo, 2007;Vanderploeg, Caron, Saunders, Katz, & Tebes, 2007;Young, Boles, & Otero, 2007). Concern over the correlation between substance abuse and child welfare, as well as growing recognition of the importance of consistency in caretaking in child development, has generated a number of policy changes on both national and state levels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Worcel, Furrer, Green, Burrus, and Finigan (2008) found that FDC children spent less time in foster care and were more likely to experience reunification than matched comparison children in the traditional court. Boles, Young, Moore, and DiPirro-Beard (2007) found that more FDC families reunified at 12, 18, 24, and 36 months than comparison families. More recently, Chuang, Moore, Barrett, and Young (2012) found that FDC participation significantly increased the likelihood of reunification, and decreased the odds that the child would reenter foster care within 12 months.…”
Section: Understanding Family Drug Courtsmentioning
confidence: 94%
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009).…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%